The Influence of Organizational Trust on Asn Commitment in Improving the Performance of The Regional Secretariat of the Southwest Papua Province - Yusuf Abdul Karim; Muh. Akmal Ibrahim; Badu Ahmad; Didik Iskandar (Journal Social Civilecial, 2025)
Organizational trust is recognized as a strategic factor influencing employees' commitment and organizational effectiveness, particularly within public sector institutions undergoing administrative transformation. This study examines the influence of organizational trust on the organizational commitment of civil servants at the Regional Secretariat of the Southwest Papua Provincial Government, one of Indonesia's newly established provincial administrations. A quantitative explanatory survey design was employed to investigate the relationship between organizational trust and ASN commitment. Data were collected from 147 civil servants selected through purposive sampling from a population of 233 employees. Organizational trust was measured through three dimensions integrity, competence, and consistency while organizational commitment was assessed using affective, continuance, and normative commitment. The data were analyzed using Structural Equation Modeling (SEM) with IBM SPSS AMOS. The findings reveal that organizational trust has a positive and significant effect on ASN commitment (estimate = 0.811; p = 0.001). All three dimensions of organizational trust significantly influence organizational commitment, with organizational consistency emerging as the strongest predictor, followed by integrity and competence. The results indicate that civil servants who perceive their organization as transparent, competent, and consistent in implementing policies exhibit stronger emotional attachment, loyalty, and willingness to contribute to organizational goals. The study extends organizational trust theory by demonstrating its strategic role in strengthening commitment within newly established regional governments characterized by institutional transition and bureaucratic adaptation. Practically, the findings suggest that strengthening transparent leadership, policy consistency, organizational capability, and equitable governance can enhance employee commitment and improve the effectiveness of public administration and regional public service delivery.